PERAN BAHASA DALAM PROMOSI KESEHATAN MENTAL: ANALISIS PSIKOLINGUISTIK PADA KAMPANYE DIGITAL - Rudi Purwana (Journal Analytica Islamica, 2024)
This study aims to analyze the role of language in promoting mental health through digital campaigns from a psycholinguistic perspective. In the digital era, social media and online platforms have become primary tools for disseminating mental health messages. The language used in these campaigns plays a critical role in shaping audience understanding, perception, and attitudes. This study employs content analysis of mental health campaign messages distributed across platforms like Instagram, Twitter, and YouTube. The primary focus is on linguistic structure, metaphor usage, positive-negative word choices, and their emotional effects. The findings reveal that empathetic, inclusive, and straightforward language enhances audience acceptance and comprehension of mental health issues. Moreover, relevant metaphors and personal narrative-based communication styles prove effective in establishing an emotional connection with the audience. This research contributes to developing more effective communication strategies for promoting mental health through digital media.